Evolution of Renal Function after Partial and Full Mechanical Support for Chronic Heart Failure. Issue 5 (May 2014) - Jacobs, Steven; Droogne, Walter; Waelbers, Valerie; Van den Bossche, Klaartje; Bollen, Hilde; Geens, Jef; Rega, Filip; Burkhoff, Daniel; Meyns, Bart
Purpose: Recently a minimal invasive, partial support continuous flow left ventricular assist device (LVAD) became available for treatment of chronic heart failure. The aim of this study was to analyze whether partial support is capable of improving kidney function in end-stage heart failure. Methods: We performed a single-center retrospective analysis of patients how received a full (n = 43) or partial support LVAD (n = 18) between 2007 and 2013. Patients on dialysis or in INTERMACS class I were excluded. Renal function was assessed until 3 months after the implantation. A calculated GFR less than 60 m/min was considered to be renal failure. Results: Creatinine level after LVAD implant decreased 23% in patients on full support (1.3 ± 0.4 mg/dl vs. 1.0 ± 0.3 mg/dl; p<0.001) and 24% in patients on partial support (1.6 ± 0.6 mg/dl vs. 1.2 ± 0.4 mg/dl; p = 0.17) within 3 months. In each group patients with a pre-operative GFR less than 60 ml/min were selected. In this subgroup there was a 35% decrease in creatinine levels for patients on full support (1.7 ± 0.4 mg/dl vs. 1.1 ± 0.5 mg/dl; p<0.01) and a 32% decrease in patients on partial support (2 ± 0.4 mg/dl vs. 1.4 ± 0.3 mg/dl; p<0.05) at 3 months. Conclusions: We observed a significant improvement in renal function in patients supported by full or partial support devices, even if the pre-operative renal function was severly impaired. The use of diuretics decreased in both groups. In chronic heart failure patients with impaired renal function, partial support is sufficient to improve renal function significantly.